Recurrent incarcerated complex ventral hernia: Case report: Hernia ventral compleja incarcerada recidivada: Reporte de caso - Aguilar-Gaibor, Carlos Ivan (2024)
Ventral hernia, characterized by abnormal protrusion of abdominal contents through a defect in the abdominal wall, is a common condition whose prevalence is increasing due to population aging and the obesity epidemic. We present the case of an 88-year-old patient with multiple comorbidities, including pulmonary thromboembolism, Parkinson's disease, and chronic venous insufficiency, who was diagnosed with a recurrent complex incarcerated ventral hernia and underwent hernioplasty using the Rives-Stoppa technique with synthetic mesh. The procedure was performed without complications, and the patient was discharged two days later. This case highlights the importance of advanced surgical techniques and preoperative evaluation in patients at high risk for complications.